Identification of Micro-plastic Contamination in Drinking Water Treatment Plants in Phnom Penh, Cambodia - Sandhya Babel; Hakk Dork (Journal of Engineering and Technological Sciences, 2021)
Micro-plastics (MP) contamination in drinking water has become a global concern. Its negative impacts on human health have been reported. This study identified the presence of MP in two different drinking water treatment plants (WTP) in Phnom Penh, Cambodia, and investigated their removal efficiency. Samples were collected from the inlet, sedimentation, sand filtration, and distribution tank to quantify the removal by each unit. An optical microscope and a fluorescence microscope were used to detect the MP in four size fractions: 6.5-20, 20-53, 53-500, and >500 µm. Fourier transform infrared spectroscopy (FT-IR) was used to identify the polymer type for particles with size fractions of 53-500 and >500 µm. The results showed that the MP counted in WTP1 were 1180.5 ± 158 p/L in the inlet and 521 ± 61 p/L in the distribution tank. In WTP2, the MP counted were 1463 ± 126 p/L in the inlet and 617 ± 147 p/L in the distribution tank. The smaller size fraction of 6.5-20 µm predominated at each sampling location. Fragments were the most abundant morphology compared to fibers in all sampling points of both plants. PET predominated and the overall percentages for the inlet tank were 28.8% and 26%, followed by PE with 27.1% and 20.8% in WTP1 and WTP2, respectively. Other common polymer types were PP, PA, PES, and cellophane, while all others accounted for less than 5%. The results of the study showed that a significant number of MP remained in the water distribution system.